2011
DOI: 10.1007/s12010-011-9174-6
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Conditions for Cellulase and Xylanase Extraction from Switchgrass Colonized by Acidothermus cellulolyticus

Abstract: Solid-state fermentation has been widely used for enzyme production. However, secreted enzymes often bind to the solid substrate preventing their detection and recovery. A series of screening studies was performed to examine the role of extraction buffer composition including NaCl, ethylene glycol, sodium acetate buffer, and Tween 80, on xylanase and cellulase recovery from switchgrass. Our results indicated that the selection of an extraction buffer is highly dependent on the nature and source of the enzyme b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
0
8
0
3
Order By: Relevance
“…The enzymes considered include pectinase (Castilho et al, 2000;Singh et al, 1999), xylanase (Heck et al, 2005;Maciel et al, 2009;Pal and Khanum, 2010;Rezaei et al, 2011), lipase (Menoncin et al, 2010), inulinase (Bender Brazilian Journal of Chemical Engineering et al, 2008;Chen et al, 2011), and manganeseperoxidase (Arantes et al, 2011). However, there have been few studies concerning the optimum conditions for cellulase extraction from SSF cultivations.…”
Section: Introductionmentioning
confidence: 99%
“…The enzymes considered include pectinase (Castilho et al, 2000;Singh et al, 1999), xylanase (Heck et al, 2005;Maciel et al, 2009;Pal and Khanum, 2010;Rezaei et al, 2011), lipase (Menoncin et al, 2010), inulinase (Bender Brazilian Journal of Chemical Engineering et al, 2008;Chen et al, 2011), and manganeseperoxidase (Arantes et al, 2011). However, there have been few studies concerning the optimum conditions for cellulase extraction from SSF cultivations.…”
Section: Introductionmentioning
confidence: 99%
“…Degradable xylanase as well as cellulase biomass is being recognized as an important enzyme, as xylanase is an indispensable enzyme in biobased industries (4,6,9). Various strains isolated from soil in a variety of locations have been screened to detect bacteria with high xylanase activities.…”
mentioning
confidence: 99%
“…They observed that multiple extractions with sonication improved the recovery of enzymes from SSF with an increment of enzyme yield more than twice that of conventional single stage extraction. Furthermore, in order to improve the enzyme recovery from SSF, it has been observed that extraction followed by diafiltration can enhance the activity recovery by removing inhibitory phenolic compounds from extracts [217]. Since the recovery and concentration steps are significant in enzyme production, employing ultrafiltration with 10 kDa cut off after solid-liquid extraction can improve the rate of enzyme recovery by about 74% [20,218].…”
Section: Downstream Processing In Ssf and Residue Reutilizationmentioning
confidence: 99%